2015
DOI: 10.3390/ijerph121114519
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposure to Radio-Frequency Electromagnetic Field Radiation (RF-EMFR) Generated by Mobile Phone Base Stations with Glycated Hemoglobin (HbA1c) and Risk of Type 2 Diabetes Mellitus

Abstract: Installation of mobile phone base stations in residential areas has initiated public debate about possible adverse effects on human health. This study aimed to determine the association of exposure to radio frequency electromagnetic field radiation (RF-EMFR) generated by mobile phone base stations with glycated hemoglobin (HbA1c) and occurrence of type 2 diabetes mellitus. For this study, two different elementary schools (school-1 and school-2) were selected. We recruited 159 students in total; 96 male student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 26 publications
0
35
1
1
Order By: Relevance
“…In rare but probable cases of fault removal activities such as antenna replacement as in the Table, there can be elevated SAR values in the heads and torsos of the maintenance people.In general, maintenance people will be exposed to base station EMR for about 2.5 h per day based on 50 sites per responsibility area. The immediate effects [3,4,12] and long-term effects [8] are available in academic studies. Recent studies showed much more subtle effects [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rare but probable cases of fault removal activities such as antenna replacement as in the Table, there can be elevated SAR values in the heads and torsos of the maintenance people.In general, maintenance people will be exposed to base station EMR for about 2.5 h per day based on 50 sites per responsibility area. The immediate effects [3,4,12] and long-term effects [8] are available in academic studies. Recent studies showed much more subtle effects [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…This exposure raises concerns and questions about the impact of the EMR on human health and life. A number of papers were devoted to the issue of bioelectromagnetic effects [3][4][5][6][7][8][9][10][11][12][13][14][15]. These include cellular, immunological, hematological, auditory level responses to EMR exposure such as heat shock protein secretions, protein leakages, cellular ion channel anomalies, blood sugar level fluctuations, and hearing loss, as well as cognitive function degradations.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a recent study, 159 students in the age range 12–17 years were recruited. [20] Ninety-six male students were from school-1 where students were exposed to high-energy RF-EMF (9.601 nW/cm 2 at a frequency of 925 MHz for a duration of 6 h daily, 5 days in a week) and 63 male students were from school-2 where students were exposed to low-energy RF-EMF (1.909 nW/cm 2 at a frequency of 925 MHz for 6 h daily, 5 days in a week). At the end, it was observed that the mean HbA1c for the students who were exposed to high-energy RF-EMF was significantly higher (5.44 ± 0.22) than the mean HbA1c for the students who were exposed to low-energy RF-EMF (5.32 ± 0.34) ( P = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that students who were exposed to high-energy RF-EMF generated by mobile phone base stations had a significantly higher risk of type 2 diabetes mellitus compared to their counterparts who were exposed to low-energy RF-EMF. [20] As compared to the above study where 2G network was used, in the present study, in view of increasing popularity, we exposed the subjects to 3G network with average RF-EMF energy of ~130.5 nW/cm 2 at a frequency of 2100 MHz. We observed that subtle energy levels of organs, including pancreas, reduced significantly after 15 min of RF-EMF exposure as compared to sham.…”
Section: Discussionmentioning
confidence: 99%
“…A mobile phone terminal, which is a type of low-power, wireless transmitter-receiver, is a source of radiofrequency-electromagnetic fields (RF-EMF) [3]. In addition, mobile phone calls require the establishment of mobile phone base stations.…”
Section: Introductionmentioning
confidence: 99%